The effect of precautions on early dislocations post total hip arthroplasty: a retrospective cohort study. Issue 5 (September 2018) - Allen, Felix C; Skinner, Daniel L; Harrison, Jane; Stafford, Giles H
Introduction: The efficacy of hip precautions in preventing dislocation post total hip arthroplasty (THA) has been questioned in recent literature. From 2014 our centre ceased routinely prescribing them due to lack of evidence. We investigate the effect of stopping these precautions on dislocation rate, patient satisfaction and Oxford hip score (OHS). Methods: Patients who underwent primary total hip arthroplasty prior to this change in protocol ( n = 2551) and for 1 year subsequently ( n = 673) were identified. Operative records were used to identify key demographic and operative data. Incidence of dislocation, OHS and patient satisfaction were extracted from the centre's electronic database. Subset analysis of those patients dislocating within 6 weeks was performed. Results: Rate of dislocation at 6 weeks in those prescribed and not prescribed precautions was 0.71% and 0.89% respectively ( p = 0.618). At 1 year this rose to 1.25% and 1.49% ( p = 0.406). Satisfaction ( p = 0.332) and OHS ( p = 0.441) at 1 year was not significantly different between cohorts. Conclusions: Cessation of prescribing routine hip precautions post primary THA does not appear to significantly affect overall dislocation rate, patient satisfaction or functional status at 1 year post-operatively.